Influence of bacterial colonization of the healing screws on peri-implant tissue - Simonetta D'Ercole; Adriano Piattelli; Giuseppe Marzo; Antonio Scarano; Domenico Tripodi (Elsevier, 2013)
Background/purpose: A bacterial adhesion to implant surfaces is a first stage of peri-implant mucositis and peri-implantitis. The aim of this longitudinal study was to examine the quantitative and qualitative biofilm formation on healing screws and the presence of periodontal pathogens in peri-implant crevicular fluid (PCF). In each of the 30 participants, one healing screw was adapted to every single implant. Materials and methods: Thirty patients, 18 females and 12 males, were selected. Thirty healing abutments were left in situ for 20, 30 and 90 days. At regular times, the presence/absence of bleeding on probing (BOP) was determined. The specific periodontal pathogens were determined in PCF, by polymerase chain reaction (PCR). After 20, 30 and 90 days, the healing screws were removed and analyzed to establish the total bacterial count by a culture method. Results: BOP+ increased significantly after 90 days. Biofilm was detected on all healing abutments and the number of cultivable oral flora showed a significant increase from 20 days to 30 days and to 90 days. At 90 days, the anaerobic counts constituted the bulk of plaque examined and Veillonella spp. were present in higher percentages levels (19.82%) among the Gram-negative bacteria. No significant differences among the experimental groups were detected in the frequencies of detection of each monitored bacteria in PCF. Conclusion: The healing screws left in situ for a period of 90 days caused a peri-implant inflammation and the presence of periodontal pathogenic bacteria in the peri-implant sulcus, due to the plaque accumulation on screw surfaces.